2022
DOI: 10.3390/pharmaceutics14050900
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Atropine in Preventing Myopia Progression: An Update

Abstract: Several approaches have been investigated for preventing myopia progression in children and teenagers. Among them, topical atropine has shown promising results and it is being adopted in clinical practice more and more frequently. However, the optimal formulation and treatment algorithm are still to be determined. We discuss the pharmacokinetic, pharmacodynamic, clinical, and tolerability profile revealed first by the multicenter, randomized ATOM 1 and 2 trials and, more recently, by the LAMP Study. Results fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 94 publications
1
17
0
Order By: Relevance
“…The combination treatments showed less rebound effect, signi cant with the dual focus lenses. Studies have shown that the rebound effect can be in uenced using different doses of atropine and method of washout [25]. A study has shown that after a year of dual-focus contact lens monotherapy, there was little to no rebound effect [26].…”
Section: Rebound Effectmentioning
confidence: 99%
“…The combination treatments showed less rebound effect, signi cant with the dual focus lenses. Studies have shown that the rebound effect can be in uenced using different doses of atropine and method of washout [25]. A study has shown that after a year of dual-focus contact lens monotherapy, there was little to no rebound effect [26].…”
Section: Rebound Effectmentioning
confidence: 99%
“…1% and 0.5%. 11 The outcome of this study is comparable to that conducted by Matteo Sacchi et al, in the European population. This study demonstrated that in the Atropine-treated group, the mean myopic progression was -0.54(0.61) D after 12 months.…”
Section: Discussionsupporting
confidence: 88%
“…Myopia is characterized by blurred vision of distant objects, which can be due to the increase in the axial length of the eye that causes the light to focus in front of the retina instead of on the retina [22]. Despite lenses and laser surgery are being largely used in the management of myopia, atropine seems to be a very effective pharmacological therapy, at least for children [23]. In fact, it is largely used in Asia, while it is less diffused in Europe because of possible side effects such as photophobia and poor visual acuity [24].…”
Section: Exploitation Of Plant Alkaloids In Ophthalmologymentioning
confidence: 99%